Hadith #2163 - Sunan Abi Dawud - Aban bin Salah bin 'Umayr أبان بن صالح بن عمير; ibn Abbas; Ibn Ishaq محمد بن إسحاق بن يسار‎; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي; Mujahid bin Jabir مجاهد بن جبر (Sunan Abi Dawud)
Muhammad bin Al Munkadir said I heard Jabir say The Jews used to say “When a man has intercourse with his wife through the vagina, but being on her back the child will have a squint, so the verse came down. Your wives are a tilth to you, so come to your tilth however you will.”
Grade: Sahih

Hadith #2235 - Sunan Abi Dawud - Aban bin Salah bin 'Umayr أبان بن صالح بن عمير; Abdul 'Aziz bin Yahya bin Yusuf عبد العزيز بن يحيى بن يوسف البكائي; Aisha bint Abi Bakr; Hisham bin 'Urwa هشام بن عروة; Ibn Ishaq محمد بن إسحاق بن يسار‎; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي; Mujahid bin Jabir مجاهد بن جبر; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
A’ishah said “Barirah’s husband was a free man when she was emancipated. She was given choice. She said “I do not like to remain with him. I have such and such (grievances)”
Grade: Sahih

Hadith #2474 - Sunan Abi Dawud - Aban bin Salah bin 'Umayr أبان بن صالح بن عمير; Amr bin Muhammad al-Anqazi عمرو بن محمد العنقزي (Sunan Abi Dawud)
Umar (may Allah be pleased with him) took a vow in the pre-Islamic days to spend a night or a day in devotion near the Ka’bah (in the sacred mosque). He asked the Prophet (ﷺ) about it. He said: Observe i’tikaf (i.e. spend a night or a day near the Ka’bah) and fast.
Grade: Sahih

Hadith #2699 - Sunan Abi Dawud - Aban bin Salah bin 'Umayr أبان بن صالح بن عمير; Abdul 'Aziz bin Yahya bin Yusuf عبد العزيز بن يحيى بن يوسف البكائي; Ali ibn Abi Talib; Ibn Ishaq محمد بن إسحاق بن يسار‎; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي; Raba'i bin Harash bin Jahsh ربعي بن حراش (Sunan Abi Dawud)
Nafi said that a horse of Ibn ‘Umar went away and the enemy seized it. The Muslims overpowered them. Khalid bin Walid returned it to him after the Prophet (ﷺ).
Grade: Sahih

Hadith #4169 - Sunan Abi Dawud - Aban bin Salah bin 'Umayr أبان بن صالح بن عمير; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; ibn Abbas; Mujahid bin Jabir مجاهد بن جبر; Usamah ibn Zayd (Sunan Abi Dawud)
Allah has cursed the woman who tattoo and the women who have themselves tattooed, the women who add false hair (according to the version of Muhammad b. Isa) and the women who pluck hairs from their faces (according to the version on ‘Uthman). The agreed version then goes: The women who spaces between their teeth for beauty, changing what Allah has created. When a woman of Banu Asad called Umm Ya’qub, who read the Qur’an (according to the version of ‘Uthman) heard it, she came to him (acc
Grade: Sahih